Challenges in developing therapeutic strategies for mild neonatal encephalopathy - Alice McDouall (Neural Regeneration Research, 2022)
There is increasing evidence that infants with mild neonatal encephalopathy (NE) have significant risks of mortality, brain injury and adverse neurodevelopmental outcomes. In the era of therapeutic hypothermia, infants need to be diagnosed within 6 hours of birth, corresponding with the window of opportunity for treatment of moderate to severe NE, compared to the retrospective grading over 2 to 3 days, typically with imaging and formal electroencephalographic assessment in the pre-hypothermia era. This shift in diagnosis may have increased the apparent prevalence of brain damage and poor neurological outcomes seen in infants with mild NE in the era of hypothermia. Abnormal short term outcomes observed in infants with mild NE include seizures, abnormal neurologic examination at discharge, abnormal brain magnetic resonance imaging and difficulty feeding. At 2 to 3 years of age, mild NE has been associated with an increased risk of autism, language and cognitive deficits. There are no approved treatment strategies for these infants as they were not included in the initial randomized controlled trials for therapeutic hypothermia. However, there is already therapeutic creep, with many centers treating infants with mild NE despite the limited evidence for its safety and efficacy. The optimal duration of treatment and therapeutic window of opportunity for effective treatment need to be specifically established for mild NE as the evolution of injury is likely to be slower, based on preclinical data. Randomized controlled trials of therapeutic hypothermia for infants with mild NE are urgently required to establish the safety and efficacy of treatment. This review will examine the evidence for adverse outcomes after mild NE and dissect some of the challenges in developing therapeutic strategies for mild NE, before analyzing the evidence for therapeutic hypothermia and other strategies for treatment of these infants.